ANALYSIS OF THE APPLICATION OF WORK DISCIPLINE AND WORK MOTIVATION IN IMPROVING THE PERFORMANCE OF NON-CIVIL SERVANTS IN THE HYGIENE SECTION AT THE STATE CIVIL APPARATUS PERSONNEL DEVELOPMENT CENTER IN BOGOR - Sunarto, Ading; Tanjung, Asridah Warni; Halimah, Imar (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This research is entitled "Analysis of the Application of Work Discipline and Work Motivation in Improving the Performance of Non-ASN Employees in the Hygiene Section at the State Civil Apparatus Personnel Development Center in Bogor. This study analyzes the application of work discipline and motivation to improve employee performance. The method used is qualitative research with a non-probability sample technique, purposive sampling. The data collection procedure of this study is observation, interview, documentation, and triangulation. Data analysis techniques in this study are data reduction, data presentation, conclusion drawing and verification, Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis, and Quantitative Strategic Planning Matrix (QSPM) analysis. The results of this study show that the application of employee work discipline is quite good because some employees obey the rules set by the agency. In addition, applying employee motivation is good because there are awards from agency leaders. The application of work discipline and work motivation can improve employee performance. Employee performance is good because the resulting performance has a good impact on individuals and agencies. The results of the SWOT analysis show that it is in quadrant I, which is aggressive, where the values of the X axis (strengths and weaknesses) and the Y axis (opportunities and threats) have positive values of 1.43 and 1.70, which means that this situation is favorable for agencies to use existing strengths to take advantage of opportunities. Also, the results of the QSPM analysis are that 5 alternative strategy priorities can be used as strategies in improving employee performance, including improving good service, employee attitudes, and employee responsibilities by 6.50, controlling work to run professionally by 6.42, maintaining good cooperative relationships between employees and other agencies by 6.13, increasing the potential ability of employees by 5.91, increased assertiveness and care by 5.22